Reported Physical and Sexual Abuse in Childhood and Adult HIV Risk Behaviour in Three African Countries: Findings from Project Accept (HPTN-043) - Richter L. (2014)
Childhood sexual and physical abuse have been linked to adolescent and adult risky sexual behaviors, including early sexual debut, an increased number of sexual partners, unprotected sex, alcohol and drug use during sex and sexual violence. This paper explores these relationships among both men and women who report histories of childhood abuse from representative samples of communities in three countries in southern and eastern Africa (South Africa, Zimbabwe and Tanzania). Data were collected as part of a 3-year randomized community trial to rapidly increase knowledge of HIV status and to promote community responses through mobilisation, mobile testing, provision of same-day HIV test results and post-test support for HIV. The results indicate that reported childhood sexual and physical abuse is high in all three settings, also among men, and shows strong relationships with a range of sexual risk behaviors, including age at first sex (OR -0.6 (CI: -0.9, -0.4, p < 0.003) - among men, OR -0.7 (CI: -0.9, -0.5, p < 0.001) - among women), alcohol (OR 1.43 (CI: 1.22, 1.68, p < 0.001) - men, OR 1.83 (CI: 1.50, 2.24, p < 0.001) - women) and drug use (OR 1.65 (CI: 1.38, 1.97, p < 0.001) - men, OR 3.14 (CI: 1.95, 5.05, p < 0.001) - women) and two forms of partner violence - recent forced sex (OR 2.22 (CI: 1.66, 2.95, p < 0.001) - men, OR 2.76 (CI: 2.09, 3.64, p < 0.001) - women) and ever being hurt by a partner (OR 3.88 (CI: 2.84, 5.29, p < 0.001) - men, OR 3.06 (CI: 2.48, 3.76, p < 0.001) - women). Individuals abused in childhood comprise between 6 and 29 % of young adult men and women living in these African settings and constitute a population at high risk of HIV infection. © 2013 Springer Science+Business Media New York.